Comparative analysis of lower limb biomechanics during unilateral drop jump landings on even and medially inclined surfaces - Ahmed Dami; Eléna Payen; Pier-Luc Isabelle; Nader Farahpour; Gabriel Moisan (PLoS ONE, 2025)
Background/purpose Lower limbs biomechanics during unilateral jump landing, a common sports maneuver, is widely studied in research. Most studies used an even surface which may not be ecologically valid in sports contexts. There is a need to explore the lower limbs biomechanics during landing on other, more challenging, surfaces. The purpose of this study was to investigate the lower limb kinematic and kinetic differences during unilateral drop jump landing from a 30 cm platform on even (DROP) and medially inclined (WEDGE) surfaces. Methods Fifteen healthy participants were recruited to take part in this laboratory-based cross-sectional study. The experimental protocol involved comparing hip, knee, ankle and midfoot angles, moments, and power between DROP and WEDGE. Results Main kinematic findings were that during WEDGE, midfoot inversion angles were smaller, and ankle eversion and plantarflexion, knee abduction and internal rotation and hip abduction angles were greater compared to DROP. Main kinetic results were that during WEDGE, midfoot inversion and adduction moments, ankle inversion moments, knee adduction moments, hip adduction and internal rotation moments, midfoot and ankle power were greater and ankle plantarflexion and adduction moments and knee internal rotation moments were smaller compared to DROP. Conclusion These adaptations highlight the intricate interaction between surface inclination and joint movements. This study’s results not only contribute valuable insights into the biomechanics of landing on inclined surfaces but also lays the foundation for future research that can refine injury prevention strategies, optimize training protocols, and enhance the overall performance and safety of athletes across various sports.